2021
DOI: 10.3390/cancers13122890
|View full text |Cite
|
Sign up to set email alerts
|

From Pathways to Practice: Impact of Implementing Mobilization Recommendations in Head and Neck Cancer Surgery with Free Flap Reconstruction

Abstract: One of the foundational elements of enhanced recovery after surgery (ERAS) guidelines is early postoperative mobilization. For patients undergoing head and neck cancer (HNC) surgery with free flap reconstruction, the ERAS guideline recommends patients be mobilized within 24 h postoperatively. The objective of this study was to evaluate compliance with the ERAS recommendation for early postoperative mobilization in 445 consecutive patients who underwent HNC surgery in the Calgary Head and Neck Enhanced Recovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Like with other guidelines, ERAS outcomes depends on adoption of ERAS guidelines . Indeed, greater compliance with ERAS has been shown to improve outcomes . Since only about 20% of included studies reported compliance with ERAS, and reporting of these estimates were too heterogeneous to include in the analysis, it is likely that mean compliance was lower than 75% and that our findings underestimate the outcomes of ERAS.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Like with other guidelines, ERAS outcomes depends on adoption of ERAS guidelines . Indeed, greater compliance with ERAS has been shown to improve outcomes . Since only about 20% of included studies reported compliance with ERAS, and reporting of these estimates were too heterogeneous to include in the analysis, it is likely that mean compliance was lower than 75% and that our findings underestimate the outcomes of ERAS.…”
Section: Discussionmentioning
confidence: 69%
“…[127][128][129] Indeed, greater compliance with ERAS has been shown to improve outcomes. [129][130][131] Since only about 20% of included studies reported compliance with ERAS, and reporting of these estimates were too heterogeneous to include in the analysis, it is likely that mean compliance was lower than 75% and that our findings underestimate the outcomes of ERAS. If compliance is important for ERAS outcomes, how can compliance be improved?…”
Section: Discussionmentioning
confidence: 90%
“…This study will assess the treatment patterns, compliance with guidelines and HPV status (for detailed information, see online supplemental table S1). [21][22][23][24] Patients in the conservative observation group will undergo routine follow-up. 25 The patients will be observed without any additional treatment.…”
Section: Definition Of Outcomesmentioning
confidence: 99%